Mucor indicus caused disseminated infection diagnosed by metagenomic next-generation sequencing in an acute myeloid leukemia patient: A case report - Shen, Meixiao; Li, Qian; Zeng, Zhaocheng; Han, Dongxu; Luo, Xiansheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background Mucormycosis commonly occurs in immunosuppressed patients with hematological diseases, which can be life-threatening. However, many cases are often misdiagnosed due to lack of specific clinical manifestations. Additionally, the traditional blood culture or serological testing, with a high false-negative rate, is time-consuming. Thus, precise and timely diagnosis of infections is essential for the clinical care of infected patients. Case presentation We report a 29-year-old Chinese man with acute myeloid leukemia (AML) who developed febrile neutropenia after the first course of induction chemotherapy. He received empirical antibiotics, which did not relieve his symptoms. No pathogen was detected by traditional microbiologic assays, while Mucor indicus was identified by metagenomic next-generation sequencing (mNGS) in the blood specimen. Liposomal amphotericin B (LAmB) was used, resulting in the patient’s temperature returning to normal. A few days later, abdominal computed tomography (CT) scan showed multiple liver abscesses; fluorescence staining, histopathology, and mNGS identified the causative agent—M. indicus. Posaconazole was combined with LAmB as long-term antifungal treatment. Finally, the patient received allogeneic hematopoietic stem cell transplantation successfully after controlled infection. During follow-up 1 year after transplantation, the number of liver abscesses was reduced to one and remained stable. Conclusion This report described the first case of an AML patient diagnosed with culture-negative disseminated infections caused by M. indicus leading to rare hepatic manifestations using mNGS of peripheral blood and liver biopsy. LAmB combined with posaconazole was given in time, resulting in a favorable outcome. mNGS is a new method that assists in detecting the probable pathogen and increases the accuracy of identifying an etiology.